Learning for Understanding: A Faculty-Driven Paradigm Shift in Learning, Imaginative Teaching, and Creative Assessment - Díaz-Lefebvre, René (Community college journal of research and practice, 2006)
This article describes an experimental pilot study begun in 1994 in the Glendale Community College (Glendale, Arizona) psychology department. The faculty-driven idea incorporated Howard Gardner's multiple intelligences theory (MI) into a new paradigm--one where creative forms of learning resulted in real understanding. The pilot study, Multiple Intelligences/Learning for Understanding (MI/LfU), was offered in 10 psychology classes over a 2-year period (1994-96). It introduced innovative ways for students to complete assignments and demonstrate learning of essential information. Based on students' "intelligences," they chose creative "Learning options," such as acting/role-playing, mime, collage, sculpture, creative dance, original poetry, musical performance, drawing/sketching and paper/pencil testing to demonstrate core concepts and principles. Learners demonstrated understanding of academic material through a "performance of understanding" as they taught concepts to their peers using their chosen learning options. Following the conclusion of the pilot study, the initiative was expanded to include teachers of other subjects (English, art, chemistry, math, biology, music, communication, child/family studies, anthropology, Spanish, nursing, psychology). In 2000, the MI/LfU expansion study became a recognized program at Glendale Community College, participating in and making significant contributions to college assessment and institutional effectiveness programs.